MiβGESCHICK: SEVERAL THESES ON THE SUBJECT OF INTERCULTURAL THEATRE SUPPLEMENTED BY SEVERAL KEY EXAMPLES THAT INCLUDE STATIONARY WRITERS, TRANSLATIONS, TRAVELLERS ON FOOT, HORSES, OR VESSELS, AND SEARCH ENGINES - LIM ENG HUI ALVIN (2010)
Master's